LITERATURE REVIEW ON THE ROLE OF LEARNING INTERESTS ON LEARNING OUTCOMES OF ELEMENTARY AND HIGH SCHOOL STUDENTS - Utami, Riska; Fariza, Jihan; Alrefi, Alrefi (Jurnal Kopendik, 2025)
This study aims to analyze the effect of learning interest on student learning outcomes at the elementary and high school levels through a systematic literature review. The research method uses a literature study by analyzing 20 journal articles published in the last 5 years. The results show that interest in learning has a significant effect on improving student learning outcomes in various subjects, with the level of influence varying from 11.6% to 85.74%. The determinants of interest in learning include internal (motivation, aspirations) and external aspects (teaching methods, parental support, school environment). The findings recommend an interest-based learning approach to improve education quality.